Authority To Regulate And Utilize Water Resources Management From Perspective Of Environmental Administrative Law In Indonesia - Firzhal Arzhi Jiwantara; Bayu Karunia Putra; Iskandar Dinata (UIN Mataram, 2026)
This study examines state authority in water resource management from the perspective of environmental administrative law amid increasing pressures on water quality, climate change, and conflicts of interest among the state, communities, and the private sector in Indonesia. Following the Constitutional Court’s decisions and the enactment of Law No. 17 of 2019 concerning Water Resources, the state is reaffirmed as the principal authority responsible for controlling and ensuring water utilization for public welfare. This research employs a normative juridical method using legislative, conceptual, and comparative approaches. Data were collected from primary legal materials, including statutes, implementing regulations, and court decisions, as well as secondary materials such as books, scientific journals, and relevant studies. The analysis uses descriptive-analytical and interpretative techniques to examine norms and principles of environmental administrative law. The findings reveal that the state exercises authority through administrative instruments such as licensing, supervision, and administrative sanctions. However, overlapping authority between central and regional governments, weak environmental oversight, and limited integration between administrative and ecological instruments reduce governance effectiveness. In addition, the principles of participation, transparency, and precaution have not been optimally implemented, affecting environmental protection and community rights to water. The study concludes that strengthening legal instruments, harmonizing authority, enhancing institutional capacity, and consistently applying principles of good governance and precaution are essential for sustainable and equitable water resource management. This article contributes by offering an integrated analysis of post-2019 water governance and its implications for environmental administrative law reform in Indonesia.